Encyclopedia of Islamic herbal medicine - Morrow, John A. (John Andrew), 1971- (McFarland, 2011)
"Combining classical Arabic primary sources with an exhaustive survey of modern scientific studies, this encyclopedia features a multidisciplinary approach which should prove useful for both practitioners and followers of herbal medicine. Entries include each herb's botanical and alternate names, a summary of its 'prophetic prescription,' its properties and uses, and a guide to related contemporary scientific studies"--